The Complexity of Measuring Complexity - Tarride-Fernandez, M (2013)
The purpose of this paper is to present a reflection that can contribute to the discussion of the possibility, or not, of measuring the complexity of any given system. The reflection takes place considering three aspects: the first one, of an etymological character, with the purpose to specify the semantics of complexity. The second, epistemological, refers to the forms of complexity measuring in different domains. And the third, of an ontological character, refers to the essential in the complexity of reality, which contains to the observer who observes and that is observes himself. It is proposed to reserve the word complex to refer to systems that are treated as an undecomposed and irreducible totality and the act of measuring does not take place; while the expression complicated may be used when the act of reduction takes place by measuring the system. The statement made claims to be revised, criticized, questioned, confronted?…?, with the aim to enrich it and accept it, or else to reject it and discard it. There is some degree of originality, with respect to other works, that deals with the measurement of complexity, but which does not refer to the distinction that it is possible to establish between complexity and complication, with its epistemological implications and in particular with the challenge of its quantification. © 2013, Emerald Group Publishing Limited